Evolution of Digital Library Management Systems: Bibliometric Analysis of Cloud Computing Technology Implementation - Saputry Wahyuni, Haria; Valentino, Rahmat Alifin (Brawijaya University Library, 2025)
Digital libraries are undergoing a significant transformation with cloud computing adoption increasing by 300% in the last decade. Although global investment is set to reach 18.5 billion by 2023, there is still a gap in comprehensive studies on global publication trends and international research collaborations. This study is relevant considering the disruption of the COVID-19 pandemic that has accelerated the digital transformation of libraries globally. This study aims to analyze the development of scientific literature on cloud computing implementation in libraries, identify patterns of research collaboration, map the evolution of the topic over the last two decades, and evaluate the dynamic relationship between cloud technology developments and library system transformation. Bibliometric analysis was conducted on 375 documents from the Scopus database (2009-2025) using Bibliometrix software in R. Data extraction included information on authors, affiliations, year of publication, keywords, and citations using a search string combining the terms digital libraries and cloud technologies. The analysis used the Bibliometrix and Biblioshiny packages, with the validity of the method confirmed through comparison with similar bibliometric studies. The analysis shows two major waves of academic interest: 2013-2015 and 2019-2021, with dominant contributions from researchers from the Asian region, especially China. Research is evolving from a focus on basic computing and simulation to the integration of intelligent and collaborative technologies. Current topics include artificial intelligence, IoT, smart libraries, and data privacy, with “digital libraries” as a central keyword, closely linked to “cloud computing” and “information systems”. The evolution of digital library management systems shows a shift from on-premises-based systems to connected ecosystems that leverage cloud technologies, AI, and data analytics. Research is interdisciplinary, involving library science, information technology, and engineering. There are opportunities for international collaboration to expand the implementation of these technologies in developing countries and bridge the global digital divide.